Analisis profitabilitas dan ukuran perusahaan terhadap initial return pada perusahaan IPO di Bursa Efek Indonesia Periode 2017-2021 - Komariah, Siti; Sabrina, Aliffia Difa (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Companies that want to maximize the value of the company need a lot of funds or capital. To obtain the funds or capital, the company can conduct an initial public offering (IPO). An IPO is the process of issuing, buying, and selling shares to the public for the first time in the framework of an initial public offering of shares. This study aims to analyze the effect of profitability and company size on the initial return of IPO companies on the Indonesia Stock Exchange. The sample in this study was 253 companies that had IPOs during the 2017–2021 period. Multiple linear regression analysis was used with cross-sectional data in this study. Testing the model in this study uses the F-test, while testing the hypothesis uses the t-test. The results of this study show that the variable